2001
DOI: 10.1088/0022-3727/34/4/326
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional compositional analysis of quantum dots

Abstract: A simulation program has been set up, which calculates the x-ray profiles of x-ray line scans taken across features of arbitrary structural and compositional geometries embedded in a matrix. The simulated scan intensities are compared to experimental scan intensities, obtained in an analytical scanning transmission electron microscope. The program is applied to calculate x-ray profiles of InAs quantum dots embedded in GaAs and to SiGe quantum dots embedded in Si in a thin foil in cross-sectional [011] projecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…These include scanning tunneling microscopy, 17 TEM with high-resolution imaging, 18 electron energy loss spectrometry, 19 x-ray energy disperse spectrometry, 20 high-resolution x-ray diffraction, 21,22 and scanning TEM. 23 Most of these techniques have shown nonuniform dot material distribution in the dots because of interdiffusion with the surrounding media. Raman scattering method used here is simple and direct, however, it can only give an average concentration of the dots.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These include scanning tunneling microscopy, 17 TEM with high-resolution imaging, 18 electron energy loss spectrometry, 19 x-ray energy disperse spectrometry, 20 high-resolution x-ray diffraction, 21,22 and scanning TEM. 23 Most of these techniques have shown nonuniform dot material distribution in the dots because of interdiffusion with the surrounding media. Raman scattering method used here is simple and direct, however, it can only give an average concentration of the dots.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the nonuniform Ge content in the dots has been proved by elemental distribution analysis using an electron energy filtering imaging method in TEM 24 and scanning TEM. 23 Simple calculations show, for example, in-plane strain to be Ϫ0.02 for an alloy with Ge concentration of 0.48 ͑samples A, B, and C͒, leading to a GeGe mode frequency of 308.3 cm Ϫ1 by using Eq. ͑1͒.…”
Section: Resultsmentioning
confidence: 99%
“…Some researchers have observed dots with hemispherical shapes; others have observed dotshapes that are multifaceted domes; and yet several other groups have reported dots with pyramidal shapes. 1 It is generally difficult to determine the shape of the dots in-situ during growth; the lateral extent and height of the dots, however, can often be determined approximately for surface quantum dots from atomic force microscope studies. Accurate measurements of buried dot-sizes can usually be obtained from transmission electron microscope studies; these studies can generally provide valuable information about the shape of the dots.…”
Section: Introductionmentioning
confidence: 99%
“…AFM studies [8] of our dot structures indicate dome-or pyramidal-shaped structures with base diameters in the range 80-120 nm, heights in the range 10-20 nm (above the wetting layer) and a surface density of around 2 Â 10 9 /cm 2 . Electron microscopy studies of the structure of similar Si/Ge dots to those studied here [9], have shown them to be composed of a Si 1Àx Ge x alloy with an average concentration of around x ¼ 0:5: The wetting layer is essentially a 4 nm thick quantum well composed of a Si 1Àx Ge x alloy with xE0:23: In terms of the hole confinement in the system, we therefore expect a valence-band offset between the dot and the surrounding silicon/ wetting layer of around 0.35 eV. There is also strong thinning of the wetting layer close to the dot creating a potential barrier around the dot for hole transfer from the wetting layer [10].…”
Section: Resultsmentioning
confidence: 70%